2010
DOI: 10.1007/s10805-010-9122-z
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships Between Ethical Climates, Ethical Ideologies and Organisational Commitment Within Indonesian Higher Education Institutions

Abstract: This research aimed to assess the potential of alternatives to extrinsic pecuniary rewards for cultivating employees' commitment in denominational higher education institutions in Indonesia. Two ethics-related variables, namely ethical climates and ethical ideologies, were chosen as possible predictors. A model delineating the nexus between ethical climates types, ethical ideologies, and various forms of organisational commitment was developed and tested. A two-step structural equation modelling procedure was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 52 publications
2
23
0
Order By: Relevance
“…Moreover, educational offices, like other educational institutions, abound with procedural manuals, regulations, and ethical codes to fulfill institutional goals, and hence they strive to develop and nurture adherence to them among educators for the sake of providing a measure of governance over the actions and behaviors of educators. In line with this interpretation, Putranta (2008) clarified that idealistic orientations could nurture among employees when they perceive their institution highly supports adherence to principles and rules. The findings also revealed that egoistic climates, namely self-interest, institutional benefit, efficiency, do exist in educational offices.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…Moreover, educational offices, like other educational institutions, abound with procedural manuals, regulations, and ethical codes to fulfill institutional goals, and hence they strive to develop and nurture adherence to them among educators for the sake of providing a measure of governance over the actions and behaviors of educators. In line with this interpretation, Putranta (2008) clarified that idealistic orientations could nurture among employees when they perceive their institution highly supports adherence to principles and rules. The findings also revealed that egoistic climates, namely self-interest, institutional benefit, efficiency, do exist in educational offices.…”
Section: Resultsmentioning
confidence: 67%
“…These findings are inconsistent with earlier studies that aimed to investigate the validity of the nine climates proposed by Cullen et al (1993) .No prior study is mentioning the emergence of all nine climates (Ambrose, Arnaud, & Schminke, 2007;Cullen, Parboteeah, & Victor, 2003;Peterson, 2002a). Previous research articles were different in terms of the number of the emergent climates which ranged from five to eight (Agarwal & Malloy, 1999;Yener et al,2012;Cullen et al,1993;Grobler, 2016;Cullen et al, 2003;Putranta, 2008;VanSandt, 2001;Vaicy, Barnett & Brown,1996;Wimbush et al, 1997). However, these findings are consistent with previous studies that concluded that distinct types of EC exist across different institutions (Agarwal & Malloy, 1999;Yener et al, 2012;Cullen et al (1993);Grobler, 2016;Cullen et al, 2003;Putranta, 2008;VanSandt, 2001; Vaicy, Barnett & Brown, 1996;Wimbush et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted by McCabe et al (2001) looked at the similarities of ethical climate and culture and found a strong overlap and important relationship between these two constructs. Putranta (2008) points out that the difference lies in the level of examination. Climate being more descriptive in nature and culture being much more evaluative and situational dependent (Van Oosterhout,…”
Section: Evaluating-assessing Ethicsmentioning
confidence: 99%
“…According to (Moran & Volkwein, 1992) in business contexts, "culture" and "climate" are two dissimilar concepts that are termed interchangeably, (Putranta, 2008).The two concepts somehow allocate similar importance in examination of individual relationship with covert psychological and social environment of the organization (Denison, 1996). The thing that matters is intensity of assessment (Putranta, 2008). Ethical culture and climate are different in perspective, theoretical implications and methodology (Denison, 1996).…”
Section: Introductionmentioning
confidence: 99%